Paparan Multi-Kontaminan dalam Air Minum dan Hubungannya Dengan Blue Baby Syndrome Pada Bayi - Sofia, Norlaila; Zubaidah, Tien; Ali As, Zulfikar (Jurnal Skala Kesehatan, 2025)
This review aims to explore the impact of chemical contaminants other than nitrates, including nitrites, lead, mercury, and arsenic, on the risk of blue baby syndrome or methemoglobinemia in infants, as well as to identify the synergistic effects of multi-contaminant exposure. A literature search was performed on prominent scientific databases, including PubMed, Scopus, and Web of Science, for articles published between 2010 and 2024. The review method involved selecting and assessing study quality using the JBI Critical Appraisal Tools. Extracted data included the chemical parameters studied, study design, sample size, and main outcomes. Meta-analysis was performed using a random-effects model to calculate odds ratios (OR) and relative risks (RR), as well as to evaluate heterogeneity between studies. From the 35 studies analyzed, the meta-analysis revealed that exposure to nitrites, lead, mercury, and arsenic significantly increased the risk of methemoglobinemia in infants. The results showed an OR of 4.8 (95% CI: 3.2-6.7) for nitrites, 3.5 (RR) (95% CI: 2.4-5.0) for lead, 2.9 (95% CI: 2.1-4.3) for mercury, and 3.9 (95% CI: 2.5-6.1) for arsenic. Furthermore, the combination of multi-contaminant exposure resulted in an OR of 6.5 (95% CI: 4.1-8.7) and demonstrated significant heterogeneity. This study highlights that chemical contaminants other than nitrates, including nitrites, lead, mercury, and arsenic, make a significant contribution to the increased risk of blue baby syndrome. The importance of comprehensive drinking water quality management and strict regulations on contaminant exposure is strongly emphasized.